The effect of dietary nitrate supplementation on resistance exercise performance: A dose–response investigation - Rachel Tan; Isabella G. Lincoln; Keonabelle K. Paniagua; Justin M. Foster; Lauren E. Wideen; Raymond T. Gerardo; Nathan J. Ornelas; Isaac Tchaprazian; Jeffrey Li; Michael Egiazarian; Samantha N. Rowland; Stephen J. Bailey; et al. (European Journal of Applied Physiology, 2025)
Dietary nitrate (NO 3 − ) can enhance skeletal muscle contractile function and explosive-type exercise by modulating type II muscle fibers; however, limited attention has been directed at exploring the optimal dosing guidelines and potential performance-enhancing effects of NO 3 − supplementation during resistance-type exercise. The purpose of our investigation was to examine potential dose–response effects of concentrated NO 3 − -rich beetroot juice on neuromuscular performance during resistance exercise. Eighteen resistance-trained men were assigned in a double-blind, randomized, crossover design, to four conditions to consume beetroot juice containing: negligible NO 3 − (PL); ~ 6 mmol NO 3 − (BR-LOW); ~ 12 mmol NO 3 − (BR-MOD); and ~ 24 mmol NO 3 − (BR-HIGH). Participants completed 1 set of vertical countermovement jumps (CMJ), 2 sets × 3 repetitions of barbell back squats, and 2 sets × 3 repetitions of barbell bench press 2.5 h post-supplementation. Plasma [NO 3 − ] increased in a dose-dependent manner ( P < 0.01). Plasma [nitrite] ([NO 2 − ]) increased in all BR conditions compared to PL ( P < 0.05), such that BR-MOD vs. BR-LOW ( P < 0.01) and BR-LOW vs. PL ( P < 0.01), but BR-HIGH was not different compared to BR-MOD ( P > 0.05). Performance was not different between conditions in CMJ, 50% one-repetition maximum (1RM) and 75%1RM back squats, or 50%1RM and 75%1RM bench press ( P > 0.05). The change in plasma [NO 2 − ] was significantly correlated with peak power ( r = − 0.65, P = 0.003), mean power ( r = − 0.52, P = 0.03), and mean velocity ( r = − 0.48, P = 0.04) during 50%1RM back squats following BR-LOW vs. PL but not in other conditions ( P > 0.05). This study indicates that dietary NO 3 − does not impact resistance exercise performance at any of the doses assessed in the current study.